Validity and Reliability of Civic Education Achievement Tests Among Senior Secondary School Students in Gusau Local Government Area, Zamfara State - Sule Muhammad; Sheu Adaramaja Lukman (Amandemen: Journal of Learning, Teaching and Educational Studies, 2026)
Assessment is a critical component of education, ensuring that intended learning outcomes are achieved and informing instructional decisions. In Civic Education, which aims to foster democratic values, civic responsibility, and national consciousness, the quality of achievement tests is particularly important. This study investigated the validity and reliability of Civic Education achievement tests among senior secondary school students in Gusau Local Government Area, Zamfara State. The study employed a descriptive survey design involving a population of 17,549 SS1–SS3 students, from which a stratified random sample of 375 students was drawn. Data were collected using a researcher-developed Civic Education Achievement Test, reviewed for content validity by experts and subjected to a pilot study to determine reliability. Descriptive statistics, including mean scores and standard deviations, were used to summarize student performance, while Content Validity Index (CVI) and Exploratory Factor Analysis (EFA) were employed to examine content and construct validity. Reliability was assessed using Cronbach’s alpha, supported by item-level analyses such as difficulty and discrimination indices. Findings revealed that all test items demonstrated strong content and construct validity, with CVI values ranging from 0.78 to 0.92 and factor loadings from 0.61 to 0.72. The Cronbach’s alpha coefficient of 0.82 indicated high internal consistency, confirming the reliability of the test. The study concluded that the Civic Education achievement test is a valid and reliable instrument for evaluating students’ knowledge and skills, and recommended that teachers adopt systematic test construction and validation practices to enhance assessment quality in Civic Education.